Cardiovascular dysregulation of miR‐17‐92 causes a lethal hypertrophic cardiomyopathy and arrhythmogenesis. Issue 4 (27th December 2012) - Danielson, Laura S.; Park, David S.; Rotllan, Noemi; Chamorro‐Jorganes, Aranzazu; Guijarro, Maria V.; Fernandez‐Hernando, Carlos; Fishman, Glenn I.; Phoon, Colin K. L.; Hernando, Eva
Abstract : MicroRNA cluster miR‐17‐92 has been implicated in cardiovascular development and function, yet its precise mechanisms of action in these contexts are uncertain. This study aimed to investigate the role of miR‐17‐92 in morphogenesis and function of cardiac and smooth muscle tissues. To do so, a mouse model of conditional overexpression of miR‐17‐92 in cardiac and smooth muscle tissues was generated. Extensive cardiac functional studies identified a dose‐dependent induction of dilated, hypertrophic cardiomyopathy, and arrhythmia inducibility in transgenic animals, which correlated with premature mortality (98.3±42.5 d, P <0.0001). Expression analyses revealed the abundance of Pten transcript, a known miR‐17‐92 target, to be inversely correlated with miR‐17‐92 expression levels and heart size. In addition, we demonstrated through 3′‐UTR luciferase assays and expression analyses that Connexin43 (Cx43) is a novel direct target of miR‐19a/b and its expression is suppressed in transgenic hearts. Taken together, these data demonstrate that dysregulated expression of miR‐17‐92 during cardiovascular morphogenesis results in a lethal cardiomyopathy, possibly in part through direct repression of Pten and Cx43. This study highlights the importance of miR‐17‐92 in both normal and pathological functions of the heart, and provides a model that may serve as a useful platform to test novel antiarrhythmic therapeutics.—Danielson, L. S., Park, D. S., Rotllan, N., Chamorro‐Jorganes, A., Guijarro, M. V., Fernandez‐Hernando, C., Fishman, G. I., Phoon, C. K. L., Hernando, E. Cardiovascular dysregulation of miR‐17‐92 causes a lethal hypertrophic cardiomyopathy and arrhythmogenesis. FASEB J. 27, 1460–1467 (2013). www.fasebj.org